Hysteretic Live Load Effect in Soil-Steel Structure - SOBÓTKA, Maciej; MACHELSKI, Czesław (Engineering Transactions, 2016)
This paper deals with the mechanical behaviour of soil-steel structures subjected to live loads. The results of the full scale experiment show that the deformation of such structures is affected not only by the location and intensity of the load, but also by the direction of its movement. The first part of the work reports the study of a railway viaduct located in Świdnica, Poland. In this study, the ST43-type locomotive is crossing the bridge one way and then back again. During such a loading cycle the deformation of the shell is registered. The graph of displacement in function of load position forms explicit hysteresis loop is presented. Taking the advantage of the observation made in this experiment, a suitable 2D model of the structure is formulated and the test is simulated numerically. It is demonstrated that even quite a simple numerical model can give reliable results. Finally, it is proved that the hysteretic live load effect is associated with non-linear behaviour of the soil backfill as well as the shell-backfill contact zone.